2016
DOI: 10.1007/s13594-016-0283-4
|View full text |Cite
|
Sign up to set email alerts
|

ACE- inhibitory and radical scavenging activities of bioactive peptides obtained from camel milk casein hydrolysis with proteinase K

Abstract: The aim of this study was to evaluate the effects of enzymatic hydrolysis of camel whole casein on their antioxidant and angiotensin-converting enzyme (ACE)-inhibitory properties. Whole camel casein was hydrolyzed by proteinase K (PK), and the hydrolysates were fractionized by ultrafiltration membranes into three fractions. Semi-preparative reversed-phase high-performance liquid chromatography (RP-HPLC) was used to differentiate the mixture of peptides in the 3 kDa permeate fractions. A fraction (F4) with pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 26 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…Therefore, it is necessary to improve the utilization rate of casein. Wang et al [6] applied the heat treatment to improve the properties of casein in yak milk; Huang et al [7] studied the impact of ultrasound on the gelling properties of casein; Rahimi et al [8] conducted enzymatic hydrolysis of casein in camel milk using protease K to obtain the bioactive peptides that scavenged free radicals. In recent years, researchers have used dynamic ultra-high pressure homogenization (UHPH) to improve the structural and functional properties of some proteins.…”
Section: Introduction mentioning
confidence: 99%
“…Therefore, it is necessary to improve the utilization rate of casein. Wang et al [6] applied the heat treatment to improve the properties of casein in yak milk; Huang et al [7] studied the impact of ultrasound on the gelling properties of casein; Rahimi et al [8] conducted enzymatic hydrolysis of casein in camel milk using protease K to obtain the bioactive peptides that scavenged free radicals. In recent years, researchers have used dynamic ultra-high pressure homogenization (UHPH) to improve the structural and functional properties of some proteins.…”
Section: Introduction mentioning
confidence: 99%
“…A wide range of bioactivities including antihypertensive, antioxidant, antimicrobial, anti-inflammatory and immunomodulatory properties have been reported in the literature for camel milk protein-derived peptides (for reviews, see: Hailu et al, 2016;Mati et al, 2016). More particularly, the antioxidant, antimicrobial and angiotensin converting enzyme (ACE) inhibitory activities of camel milk protein hydrolysates appear to have been studied (Jrad et al, 2014;Kumar, Chatli, Singh, Mehta, & Kumar, 2016;Moslehishad et al, 2013;Rahimi et al, 2016;Salami et al, 2010). In certain instances more potent bioactivities (antimicrobial, ACE inhibition and antioxidant activity) have been reported for camel compared to bovine milk hydrolysates and fermentates (Moslehishad et al, 2013;Salami et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Proteinase K was selected based on our previous work with camel milk casein, where we reported that the peptide fractions resulted from proteinase K digestion had the best antioxidant properties. [13]. Thus, proteinase K was used in the current study to evaluate its effect on walnut proteins.…”
Section: Methodsmentioning
confidence: 99%